Implementasi Model Pembelajaran Flipped Classroom Berbantuan E-Book Interaktif Untuk Meningkatkan Kompetensi Literasi Sains Materi Vektor - S.Pd., M.Pd.I, Subkannayla (Balai Diklat Keagamaan Surabaya, 2023)
The purpose of this study was to determine the increase in scientific literacy competence in vector material by implementing the flipped classroom learning model with the help of interactive e-books. This research is in the form of best practice in implementing learning with research samples of class X IPA-1 students at MAN 2 Mojokerto. The results of the research analysis showed that the classical average value had a significant increase from the pre-test value of 49.67 to 84.52 in the post-test and the completeness of student learning outcomes also increased from 37% in the pre-test to 93% in the post-test. The implementation of the flipped classroom learning model assisted by interactive e-books can improve vector material science literacy competence and become the best experience (best practice) for teachers and have a positive impact on learning activities carried out by teachers.